(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
The economic- Arabic relations reflect , without any doubt, the debate of the relation held between development and what is not developed ; on the basis that these two phenomena form the two polar of the Arabic economic as a system resulted out of the correlation nature presented between the Arabic world and the outer world. Accordingly, the present study focuses on the in- between Arabic trade exchanges. There are many factors which relate the Arabic countries with each other . They all contribute in paying these exchanges through different historical decades. The trade relations between the Arabic countries have taken their manner from the base of the nonequivalent development which is related in the distribution of the colonial work which imposed the specialization , on the Arabic countries , in the production of the real materials, consumed what is made in the capital states and blended or fused in the world market. After the independence of the Arabic countries , their products of oil represented the maximum ratio of all their in- between and state trade. The importance of the research is implied in that the Arabic Homeland is characterized by a strategic important location and has a huge wealth enables him to depend on itself . This can be done by making use of these materials, typically, through the Arabic cooperation approaching the Arabic economic blending that can compensate the fusion with the capital economics. The research aims at investigating the return ( comeback) of the adaptations of the Arabic- Arabic relationships and the necessity of directing and associating the Arabic and economic binary and wholly relations for the purpose of serving the national goals . It is hypothesized that there is what makes the different factors of problems prominent in the in- between Arabic trade exchanges and their relation with the outer world . This leads to the decrease of the ratio of the in- between exchanges (9%) as compared to the ratio of the state exchanges (91%).